STUDI KASUS: PENERAPAN EDUKASI KEWASPADAAN STANDAR DALAM PEMASANGAN INFUS TERHADAP PENURUNAN KEJADIAN PHLEBITIS DI RUANG HARDJA SAMSURJA 1B RUMAH SAKIT BHAYANGKARA TK. I R. SAID SUKANTO - Anastasya Nurcahyani (2022)
Intravenous (IV) therapy is a procedure of inserting a catheter tip into a vein so that intravenous fluids can be drained through an IV line. The purpose of this therapy is for fluid resuscitation, access to medication, blood transfusion, and blood sampling. The frequency and duration of infusion affects the level of phlebitis risk. Phlebitis is inflammation of the veins, which is manifested by redness (rubor), heat (calor), pain (dolor), swelling (tumor), and the area of the insertion or around the vein feels tense. Data on the incidence of phlebitis according to WHO per year reaches 5%. A survey conducted by WHO in 55 hospitals spread across 14 countries (Europe, Eastern Mediterranean, Southeast Asia, and Western Pacific) found that 8.7% of patients in hospitals experienced phlebitis. The incidence of phlebitis in Indonesia reaches 9.80%. In Hardja room 1B Bhayangkara Hospital Tk. I R. Said Sukanto found the incidence of phlebitis in 2020 was 282 cases. This writing aims to see the effect of applying standard precautions in infusion to the incidence of phlebitis in the Hardja 1B room at Bhayangkara Hospital Tk. I R. Said Sukanto. The results of observations showed that there was a change in understanding related to thrombophlebitis from 50% to 87.5%, duration of infusion from 37.5% to 87.5%, documentation of infusion installation from 37.5% to 75%, and the effect of choosing the insertion site. from 62.5% to 100%. Nurses are expected to apply and increase standard precautions in infusion so as to minimize the incidence of phlebitis.